The effect of the feed particle size on the growth and survival of milkfish (chanos chanos) forsskal fry. - Miravite, Janire C. (College of Fisheries, University of the Philippines, 2013)
This study aimed to investigate the suitable particle size of a commercial pellet feed that wikl give a best result on the growth of milkfish fry. The experiments were done into two separated feeding trials: a) first feeding trial was pperformed only for 15 days using a 21-day fry and b) the second feeding trial was also performed for 15 days using a fish that were obtained from the first experiment and fish was randomly distributed. Experiments were performed in 12 rectangular glass aquaria with controlled salinity, DO, pH and water temperature. The first feeding trial consisted of four sizes of feed particles (69,150, 300 and 500~km) with three replicates each. Results on the specific growth rate (SGR), survival rate, body total length, PER and FCE were not influenced significantly by the different feed particle size. In the second experiment of feeding trial, another set of found different feed particle size were introduced (500, 840, 1000 and 1410~km). Results showed that particle size 840 ~km, greatly influence the specific growth rate (SGR) and body total length of the fish. The FCE, PER and the survival rate of the fish have no significant difference. Growth rate ws found to be closely related to feed size. Maximum growth in each case was shown only in one size of particle; larger and smaller sizes resulted in reduced growth. The particle size of maximum growth increased in direct proportion of fish length. Based on those findings, recommendations were made on the optimum feed particle size for milkfish fry.